Cabotegravir: its potential for antiretroviral therapy and preexposure prophylaxis - Stellbrink, Hans-Jürgen; Hoffmann, Christian (Current opinion in HIV & AIDS, 2018)
Analyzing the evidence for the strand transfer integrase inhibitor cabotegravir (CAB; GSK744, GSK1265744), its properties and differences from other compounds in the class, as well as reviewing the preclinical and clinical evidence for its potential in antretroviral therapy and medical HIV prevention. CAB has been investigated both as an oral and an injectable compound. Recent results show that it has promising properties with regards to its potential for parenteral maintenance therapy in combination with other compounds in HIV-infected patients currently suppressed on oral agents, as well as in preexposure prophylaxis. The strand transfer integrase inhibitor CAB is currently being investigated as an intramuscular preparation with a long half-life allowing for four to eight-weekly injection intervals, and as an oral preparation. The latter is currently only used in trials for achieving an undetectable viral load in antiretroviral-naive patients, assessing tolerability, and covering phases of suboptimal exposure to the parenteral preparation. Phase 2 trials of a dual regimen of CAB and rilpivirine have demonstrated promising virological activity in oral as well as in parenteral therapy, which are currently investigated in phase three trials. Moreover, CAB protected macaques from experimental simian/human immunodeficiency virus infection and showed promising tolerability in the first trial in humans for preexposure prophylaxis of HIV infection. CAB might, therefore, provide the basis of the new treatment paradigm of parenteral treatment and prevention of HIV infection.